Reaction to ambiguity as a signal for tax reporting aggressiveness: Evidence from German income tax return data - Daniela Kühne (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2020)
This study introduces and tests the applicability of a signal for individual tax reporting aggressiveness using German income tax return data. Tax aggressiveness is often defined as dealing with uncertainty - or more precisely: ambiguity - in an exploitative manner. In other words, firms and individuals are considered tax aggressive if they interpret ambiguous regulations in their favor. It is empirically assessed whether the way individual taxpayers deal with ambiguity in the tax system may serve as a valid indicator for more or less aggressive reporting behavior using a specificity in the German income tax system leading to uncertainty about taxable income. The decision whether to exploit ambiguity or not is attributed to differences in an intrinsic motivation to comply. It is investigated whether and to what extent taxpayers interpreting ambiguity in their favor arrive at a lower tax burden. The results show that taxpayers exploiting ambiguity in the investigated field arrive at a significantly lower effective tax rate than comparable taxpayers not exploiting ambiguity. It is concluded that the former incur lower psychic costs when using tax positions with uncertain consequences and that exploiting ambiguity can serve as an indicator for more aggressive reporting behavior. More aggressive reporting behavior is analyzed as a dependent variable to study the factors shaping it.
Keywords: H24; H26; D91; 650; tax aggressiveness; nonbusiness tax